Assessment of relative bioavailability of two presentations of moroctocog alfa (AF‐CC) in subjects with moderately severe or severe hemophilia A. Issue 3 (27th October 2014) - Shafer, Frank; Charnigo, Robert J.; Plotka, Anna; Baumann, James; Liang, Yali; Korth‐Bradley, Joan
Abstract An open‐label, single‐dose, randomized, two‐period, cross‐over study comparing the pharmacokinetics of factor VIII activity in plasma (FVIII:C) after administration of a new presentation of moroctocog alfa containing 3, 000 IU in a dual‐chamber syringe and the combined contents of approved 1, 000 and 2, 000 IU vials was conducted in 16 male subjects who had moderately severe or severe hemophilia A (FVIII:C ≤2 IU/dL). Blood samples were collected for 72 hours after administration of the dose. FVIII:C were assayed using a chromogenic substrate assay in a central laboratory. The FVIII:C pharmacokinetic parameters were calculated using noncompartmental analysis. The dual‐chamber syringe would be bioequivalent to the combined contents of the vials if the 90% confidence limits of the ratio of the geometric mean values of AUCinf, and Cmax fell within the interval of 80–125%. The bioequivalence criteria were met. A total of seven treatment related adverse events were observed in a total of five subjects. All were mild and none was determined to be related to administration of study medication.